THE STANDARDS AND ISSUES OF GOLD ZAKAT (JEWELRY) AND AL URF - Ab Rahman , Siti Maziah; Shaari , Rustam; Nik Din , Nik Muniyati; Abdul Wahid , Khalid; Mohd Zaki , Adeeba Najihah (Journal of Islamic, Social, Economics and Development, 2024)
The practices and challenges of gold zakat (jewellery) in Malaysia involve the application of the concept of "urf" (customary practice) in determining the obligation of zakat on gold jewellery. The urf rate varies across different states in Malaysia, with some states having different rates for gold jewellery worn throughout the year compared to that worn only once. The urf rate is used to determine the minimum weight of gold jewellery that is required to be issued zakat, which is calculated at 2.5% of the total weight of gold. The study highlights the importance of understanding the urf rate in each state to ensure compliance with zakat regulations. The urf rate is not only based on the weight of gold but also on the local customs and practices of the Muslim community. The study emphasizes the need for efficient methods of implementing zakat for gold jewellery, as the current system can be confusing and may lead to misunderstandings about the obligation of zakat. The study also discusses the challenges faced in implementing zakat for gold jewellery, including the lack of awareness among the public about the urf rate and the need for religious lectures to educate the community. The study concludes that improving the understanding and awareness of the urf rate can increase the collection of zakat for gold jewellery.